Nonclinical characterization of ICVB-1042 as a selective oncolytic adenovirus for solid tumor treatment - Yu Kato; Nathaniel Rice; Michael Pokrass; Jinkil Jeong; Ruben Rodriguez; Jessica J. Field; Heba Nowyhed (Communications Biology, 2024)
Abstract ICVB-1042 is an oncolytic adenovirus containing modifications to enhance replication, lysis, and viral spreading in tumor cells. The anti-tumor activity, immune activation, tropism, selectivity, and mechanism of action were evaluated in preparation for a first-in-human study. ICVB-1042 was at least 100-fold more cytotoxic in A549 cells than in normal primary cells tested, demonstrating its high tumor selectivity and a low likelihood of targeting primary tissues. ICVB-1042 administered to mice intravenously or intratumorally was effective in reducing tumor burden. Its intravenous administration also inhibited tumor growth in orthotopic models. ICVB-1042 was well tolerated in mice compared to HAdV-C5 (Wt Ad5), with reduced liver sequestration, supporting safety of the drug for systemic delivery. These preclinical data demonstrating the safety and potency of ICVB-1042 for treatment of various solid tumors support the ongoing clinical investigation (NCT05904236).